Characterisation of cardiac protein changes post death: pilot study - Mokaila, Dipolelo (Department of Medicine, 2025)
Background: Postmortem interval (PMI) is an important consideration in medicolegal death investigation. There are various approaches used in the estimation PMI also known as time since death. Methods such as temperature measurement, evaluation of muscle contraction, lividity and decomposition rate are applied to estimate PMI. These methods are however affected by environmental factors that either delay or accelerate some of the processes. Scientific evidence has revealed that the expression, concentration, and stability of proteins do not remain the same after death. This changing nor varied behaviour of proteins within the body has prompted number of research that characterise protein as a way to estimate time elapsed since death also known PMI. Furthermore, it is through interaction of proteins with other micro molecules that crucial signalling pathways and cellular processes are functional and often drive mechanisms leading to healthy and disease of organism, as a result these changes can be studied to gain insight into disease pathophysiology. There is a need to evaluate the structural integrity of tissues during the PM to see whether they might serve as a control for research. This implies that before using these tissues as controls, biomolecule stability in these tissues needed to be assessed. Therefore, it is equally crucial to investigate how these biochemical parameters change across brief PMIs in order to guide research on the selection of control tissues and their potential as an additional technique for PMI estimation. We aimed to understand biochemical changes that occur postmortem in cardiac tissues through analysis of proteins. Moreover, to determine if there was degradation in cardiac proteins post death for bodies with known time since death. Additionally, to determine the usability of PM cardiac tissues as controls for research from cardiac protein integrity over time PM. Methods: This was a cross-sectional, observational, and descriptive study. Changes in native cardiac troponin Cardiac troponin I, vinculin, and eukaryotic elongation factor (eEf1a) and their degradative products were evaluated in cardiac tissue using Western blot(WB) assay from decedents recruited at the Salt River Mortuary(SRM), Cape Town. The native and degradative products of these proteins were compared between samples collected at different times postmortem to determine whether and how much each protein has degraded. Image J analysis of protein intensities of native bands and degradative products were used to compare proteins from different PMI. Results: Recruited and sampled 52 decedents. 30 cases were sampled at PMI of greater than 72 while only 22 were sampled at PMI of less than 72 hours . Our western blot detection of 117kda vinculin protein showed this to be present in all left ventricle(LV) samples analyses. The degradation of this protein commenced at 37 hours and progressed with time in LV and could be detected beyond 3 days. In aortic valve (AV) this protein was intact in tissues extracted from living individuals and cases with early PMI of less than 24 hours. Mitral valve vinculin protein was detected from 8-57 hours postmortem and could not detect this protein beyond 91-hours. This protein in MV protein didn't show any evidence of degradation bands. cardiac troponin T native protein in LV was present in all investigated cases. This protein showed degradation bands in all cases with intensity increasing as time progressed. Cardiac troponin I detection in LV was present in majority of the cases expect for 48 and 57 case which may be due to improper sample handling or storage. However, this did not depict any degradation band but there was evidence of decrease in the native band intensity with increasing PMI hours. Lastly, we detected for eEfa1 in LV, and we found this to be present in majority of cases and the band intensities also decreased with increasing PMI. Conclusion: The aim of the study was to understand biochemical changes that occur postmortem in cardiac tissues through analysis of biochemical molecules. The results showed change of proteins in tissues with progressed time in postmortem. This may suggest that these protein biomarkers may be suitable to be used in PMI estimation. Additionally, the study noted integrity of protein at < 8 hours in postmortem depicting that cases sampled at that time may be suitable to be utilised as control for research.